Magnitude and Uncertainty of Nitrous Oxide Emissions From North America Based on Bottom‐Up and Top‐Down Approaches: Informing Future Research and National Inventories. Issue 23 (29th November 2021) - Xu, R.; Tian, H.; Pan, N.; Thompson, R. L.; Canadell, J. G.; Davidson, E. A.; Nevison, C.; Winiwarter, W.; Shi, H.; Pan, S.; Chang, J.; Ciais, P.; et al.
Abstract: We synthesized N2 O emissions over North America using 17 bottom‐up (BU) estimates from 1980–2016 and five top‐down (TD) estimates from 1998 to 2016. The BU‐based total emission shows a slight increase owing to U.S. agriculture, while no consistent trend is shown in TD estimates. During 2007–2016, North American N2 O emissions are estimated at 1.7 (1.0–3.0) Tg N yr −1 (BU) and 1.3 (0.9–1.5) Tg N yr −1 (TD). Anthropogenic emissions were twice as large as natural fluxes from soil and water. Direct agricultural and industrial activities accounted for 68% of total anthropogenic emissions, 71% of which was contributed by the U.S. Our estimates of U.S. agricultural emissions are comparable to the EPA greenhouse gas (GHG) inventory, which includes estimates from IPCC tier 1 (emission factor) and tier 3 (process‐based modeling) approaches. Conversely, our estimated agricultural emissions for Canada and Mexico are twice as large as the respective national GHG inventories. Plain Language Summary: Nitrous oxide (N2 O) is the third most important greenhouse gase (GHG) after CO2 and CH4 causing global warming. Among world regions, North America (defined herein as U.S., Canada, and Mexico) is the second largest source of N2 O emissions globally, and previous source estimates for this region vary widely. This study aims to provide a comprehensive N2 O assessment over North America including all available estimates based on a number of approaches. We report total emissions, and emissions from four anthropogenic source sectors, over the past four decades. Agriculture and industry are two major N2 O sources in North America. Our results show a minor increase in the total N2 O emission due to agricultural trends in the U.S. Our bottom‐up estimate of U.S. agricultural N2 O emissions are close to those in the EPA national GHG inventory that includes both empirical and model results. The high consistency suggests the need to take process‐based modeling results into account for future national GHG inventories. Key Points: North American N2 O emissions during 2007–2016 are estimated at 0.9–3.0 Tg N yr −1 using a combination of bottom‐up and top‐down approaches North American anthropogenic N2 O emissions grew by ∼0.2 Tg N during 1980–2016; U.S. agriculture was the largest cause of that growth Our modeled N2 O fluxes reflect an IPCC tier 3 approach, and can improve greenhouse gase inventories that largely use tier 1 and tier 2 approaches